International snap bean seed production and distribution - Emery, G.C.; Belt, J; Henry, Guy (International Center for Tropical Agriculture, 1990)
Commercial seed production in Europe and North America is a highly specialized industry. This paper discusses some of the aspects of seed production, with emphasis on the snap bean seed industry in the United States. Snap bean seed production in Australia, Europe and East Africa is also highlighted, as is the state of international snap bean seed trade. Low quality seed inhibits improved snap bean production throughout the developing world. The snap bean seed market in Colombia is used as a case study to probe the dimensions of the problem. In the absence of effective public or private sector seed distribution systems, it is suggested that the development of small-scale artesanal seed production may be an alternative to improve Colombian snap bean production. (AS)